Black and White Like Me - Barresi, John (Studia Psychologica: Theoria et praxis, 2008)
John Griffin’s classic on racism, Black Like Me (1960), provides an interesting text with which to investigate the development of a dialogical self. Griffin becomes a black man for only a short period of time, but during that time he develops a black social identity, and sense of personal identity, that contrasts radically with his former white identity. When he looks into a mirror on several occasions he engages in a dialogue with himself, as both a black and a white person. At first these two identities are so different that there is no “sympathy” between them. But through his experience, he eventually overcomes the dichotomy of two opposing selves, and acquires a personal identity, neither white nor black, but just human. In this article, I trace the development of these dialogical selves and the emergence of this new human identity. Key words : identity, racism, self, black, white